Accurate Autonomous Landing of a Fixed-Wing Unmanned Aircraft under Crosswind Conditions. Issue 17 (2016) - de Bruin, Andrew; Jones, Thomas
Abstract: The unpredictability of crosswind effects often complicate the final approach and landing procedure of any aircraft. A control system architecture with strong disturbance rejection characteristics for Unmanned Aircraft is presented, where the primary objective is to accurately land a fixed-wing aircraft under adverse weather conditions. A synergistic controller architecture is presented, where the aim is to design a structure capable of executing one of three landing techniques, or combination thereof, by simply activating various controllers at different stages of the landing phase. An acceleration-based controller architecture is used for the inner-loop controllers to reject disturbances at the acceleration level before they manifest as deviations in inertial position and velocity. A normal specific acceleration controller is augmented to exploit the high-bandwidth capabilities of direct lift control by actively using flaps to generate lift. Various crosswind landing techniques, developed for manned aircraft, are investigated and emulated by the controllers to exploit the advantages of each technique. Results show that the controllers are able to accurately land the aircraft within 0.5m of the intended touchdown point, and that the amount of lateral deviation on the runway can be minimised when controller sequencing is effectively used to align the landing gear with the direction of travel on the runway.